Drug resistance and IS6110‐RFLP patterns of Mycobacterium tuberculosis in patients with recurrent tuberculosis in northern Thailand. (27th January 2013) - Sukkasem, Supaporn; Yanai, Hideki; Mahasirimongkol, Surakameth; Yamada, Norio; Rienthong, Dhanida; Palittapongarnpim, Prasit; Khusmith, Srisin
Abstract The emergence of drug resistant Mycobacterium tuberculosis has become a global threat to tuberculosis (TB) prevention and control efforts. This study aimed to determine the drug resistance profiles and DNA fingerprints of M. tuberculosis strains isolated from patients with relapsed or retreatment pulmonary TB in Chiang Rai province in northern Thailand. Significant differences in multidrug resistance (MDR) (P = 0.025) and resistance to isoniazid (P = 0.025) and rifampin (P = 0.046) between first and second registrations of patients with retreatment TB were found. However, there were no significant differences in resistance to any drugs in patients with relapsed TB. The rate of MDR‐TB strains was 12.2% among new patients at first registration, 22.5% among patients with recurrence who had previously undergone treatment at second registration and 12.5% at third registration. Two retreatment patients whose initial treatment had failed had developed MDR‐TB with resistance to all TB drugs tested, including rifampin, isoniazid, streptomycin and ethambutol. IS6110‐RFLP analysis revealed that 66.7% (10/15 isolates) of MDR‐TB belonged to the Beijing family. In most cases, IS6110‐RFLP patterns of isolates from the same patients were identical in relapse and retreatment groups. However, some pairs of isolates from retreatment patients after treatment failure had non‐identical IS6110‐RFLP patterns. These results suggest that, after failure and default treatment, patients with retreatment tuberculosis have a significantly greater risk of MDR‐TB, isoniazid and rifampin resistance than do other patients.